Strengthening the delivery of sexual and reproductive health to women amidst the threat of ongoing corona virus disease 2019 pandemic - Saurabh R Shrivastava; Prateek S Shrivastava (Wolters Kluwer Medknow Publications, 2020)
The ongoing Corona Virus Disease-2019 (COVID-19) pandemic has emerged as one of the top most public health priorities and that all the global population is at the risk to acquire the infection. However, amidst all these developments, it should not happen that the needs of the women and girls are ignored by the public health authorities. It is very much obvious that women and girls are more exposed to the risk of acquiring the infection and also that their essential sexual and reproductive health needs will take a back seat. Moreover, we hope that the issue of maternal health continues to remain a public health priority across all nations and under no circumstances, pregnant women are deprived of routine quality assured health care, access to information & counseling for safe delivery and infection control strategies in the health care establishments. In conclusion, amidst the battle of mankind against the COVID-19 infection, the need of the hour is to simultaneously ensure uninterrupted delivery of gender-sensitive services as the consequences of the disease for women and girls goes way beyond the caseload and attributed mortality.